â€˜Ä€Ê¼isha Bint al-ShÄá¹iâ€™s Thoughts on TarÄduf and Their Implications for the IstinbÄá¹ of Law - Imran, Maizul; Ismail, Ismail (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2019)
As a book containing miracles, in literature, the miracles of the Quran have been proven by Ê»Ä€Ê¼isha Bint al-ShÄá¹iÊ¼ through her theory iâ€˜jÄz lughawÄ«. She showed the importance of the correct method of interpretation of the QurÊ¼an from aspects of tarÄduf (synonym). However, despite following the rule of